Influence of Psychological, Anthropometric and Sociodemographic Factors on the Symptoms of Eating Disorders in Young Athletes - Fortes, Leonardo de Sousa; Almeida, Sebastião de Sousa; Ferreira, Maria Elisa Caputo (Paidéia (Ribeirão Preto), 2014)
The aim of the current study was to analyse the influence of psychological, anthropometric and sociodemographic factors on the risk behaviours for eating disorders (ED) in young athletes. Participants were 580 adolescents of both sexes. We used the Eating Attitudes Test (EAT-26), the Body Shape Questionnaire and the Commitment Exercise Scale to assess the risk behaviours for ED, body image dissatisfaction (BD) and the degree of psychological commitment to exercise (DPCE), respectively. Participants’ weight, height and skinfold thickness were measured. A multiple regression indicated that BD and percentage of fat significantly modulated ( p